THE EFFECT OF EMOTIONAL INTELLIGENCE, HUMAN RELATION AND LEADERSHIP STYLES ON EMPLOYEE PERFORMANCE AT THE LOKA REHABILITATION BNN BATAM - Amelia Widya Saputri, Meta; Ngaliman, Ngaliman; Indrayani, Indrayani; Khaddafi, Muammar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The purpose of this study was to determine and analyze the effect of emotional intelligence, human relations and leadership style on employee performance in Loka Rehabilitasi BNN Batam. The research method used in this research is quantitative method. The population in this study were all employees at the agency totaling 90 people, with a sample size of 74 people. The data used in this study are primary data, namely by using a questionnaire made with a Likert scale. Data analysis techniques are quantitative data analysis techniques using statistical methods. Based on the results of data analysis, it was found that emotional intelligence had a positive and significant effect on employee performance variables, human relations had a positive and significant effect on employee performance variables, leadership style had a positive and significant effect on employee performance variables.